GASFLOW-MPI: A Scalable Computational Fluid Dynamics Code for Gases, Aerosols and Combustion. Band 1 (Theory and Computational Model (Revision 1.0) und Band 2 (Users' Manual). (KIT Scientific Reports ; 7710 und 7711) - Xiao, JianjunTravis, JackRoyl, PeterNecker, GottfriedSvishchev, AnatolyJordan, Thomas (KIT Scientific Publishing, 2016)
Karlsruhe Institute of Technology (KIT) is developing the parallel computational fluid dynamics code GASFLOW-MPI as a best-estimate tool for predicting transport, mixing, and combustion of hydrogen and other gases in nuclear reactor containments and other facility buildings. GASFLOW-MPI is a finite-volume code based on proven computational fluid dynamics methodology that solves the compressible Navier-Stokes equations for three-dimensional volumes in Cartesian or cylindrical coordinates.